Adjustments in Indigenous peoples' forest use and management in the context of climate change: a global systematic literature review. (1st September 2022) - Bauer, T.
The global diversity of forest use and management responses of forest-dependent Indigenous peoples to climate change remains poorly understood and lacks synthesis. Yet, such knowledge is essential for informed policy decisions and inclusive mitigation strategies. Through a systematic literature review, forest-dependent Indigenous peoples' responses to climate change and extreme weather events were analysed, including the prevalence of the strategies, their drivers, the role of sensitivity to climate change and the integration of traditional ecological knowledge (TEK) in forest use and management. Also, an assessment was made of how forest dependence and traditional knowledge are acknowledged in Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs). The results show knowledge clusters around coping and adaptation, mitigation, and joint strategies in North and South America and Asia. Multiple Correspondence Analysis showed that articles documenting adaptations trategies were associated to a reactive response time, Indigenous peoples as drivers and the integration of TEK and information on their climate sensitivity. The diversity of applied strategies found, mostly related to non-timber forest products (NTFPs), comprised ecologically sustainable and unsustainable practices. Mitigation s trategies, mostly REDD+ projects, which were significantly associated with proactive and external initiatives, largely omitted information on the sensitivity of the studied Indigenous group and the involvement of traditional knowledge. Joint strategies seem to be a good compromise of participatory efforts and were largely linked to integrating Indigenous peoples' traditional knowledge. Knowledge gaps include evidence of forest-related resilient livelihood strategies. Future research should focus on participatory and sustainable climate measures, the role of TEK and the drivers for the success of forest-related climate responses, as well as the potential effectiveness of joint adaptation-mitigation measures for forest-dependent Indigenous peoples on a global scale.